Immigration-Related Diversity and Trust in German Cities: The Role of Intergroup Contact - Stolle, D; Petermann, S; Schmid, K; Schönwälder, K; Hewstone, M; Vertovec, S; Schmitt, T; Heywood, J (2013)
This article investigates the relationship between neighbourhood diversity, various forms of intergroup contact and trust in a sample of native Germans clustered in 50 neighbourhoods in several German cities. The authors argue that the consideration and direct measurement of intergroup contact is essential for fully comprehending the consequences of rising ethno-cultural diversity in Western democracies. Our results show that neighbourhood immigration-related diversity in itself does not exert the same negative effects on generalized and outgroup trust as found in the North American context. Instead, intergroup contact moderates the effects of neighbourhood diversity. The results add to our understanding of the different socio-political consequences of immigration-related diversity and immigrant contact in social networks. © 2013 Copyright Elections, Public Opinion and Parties.